Using a Systems Engineering Initiative for Patient Safety to Evaluate a Hospital-wide Daily Chlorhexidine Bathing Intervention. Issue 4 (October 2015) - Caya, Teresa; Musuuza, Jackson; Yanke, Eric; Schmitz, Michelle; Anderson, Brooke; Carayon, Pascale; Safdar, Nasia
<x xml:space="preserve">Abstract</x> We undertook a systems engineering approach to evaluate housewide implementation of daily chlorhexidine bathing. We performed direct observations of the bathing process and conducted provider and patient surveys. The main outcome was compliance with bathing using a checklist. Fifty-seven percent of baths had full compliance with the chlorhexidine bathing protocol. Additional time was the main barrier. Institutions undertaking daily chlorhexidine bathing should perform a rigorous assessment of implementation to optimize the benefits of this intervention.